Potential Health Benefits of Fruits and Vegetables II - Mazzoni, Luca; Fernández, Maria Teresa Ariza; Capocasa, Franco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Both vegetables and fruits, as plant-based foods, are known for their abundance of bioactive compounds, which play a crucial role in disease prevention. Researchers from various disciplines have dedicated significant efforts to understanding the compositions of these bioactive compounds and exploring how fruits and vegetables contribute to promoting health and preventing diseases. This reprint presents studies on the composition of bioactive compounds found in the main fruit and vegetable species, their health effects when consumed fresh or processed, and their mechanisms of action against human diseases, including in vitro and in vivo models.